2017
DOI: 10.2739/kurumemedj.ms6403
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cadaver Injection Method Using Latex and Magnetic Fluid

Abstract: Summary:Vascular injection into extracted tissue may be associated with leakage due to excessive local injection pressure. Historically, this complication has been impossible to resolve because the injection pressure has been the only available force with which to send the agent to the peripheral vasculature. We have developed a new vascular injection method that utilizes a material affected by magnetic force and is therefore not solely dependent upon the injection pressure.We mixed the same weights of latex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…17 was toxic and required a fumigation hood. Watanabe et al described a method of using magnetic dye 9 to help improve uptake of dye into the cadaver, but we found that such methods were expensive, and would be difficult to obtain. Latex was a cheap, water-soluble, flexible, and elastic product; hence, it was our preferred choice.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…17 was toxic and required a fumigation hood. Watanabe et al described a method of using magnetic dye 9 to help improve uptake of dye into the cadaver, but we found that such methods were expensive, and would be difficult to obtain. Latex was a cheap, water-soluble, flexible, and elastic product; hence, it was our preferred choice.…”
Section: Discussionmentioning
confidence: 88%
“…This simple application of physics would also obviate the need for injection pumps that are costly or avoid the use of special magnetic devices to push fluid along. 9 10 In the case of veins, the valvular patency has to be considered. Retrograde preparation and infusion of the vein may not be possible and could even rupture the vein due to the presence of valves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation